Maria conversa - Portillo, Blanca, 1963-; Tóibín, Colm, 1955- (Testamento : Artisan Films, 2016)
Maria Converses follows the actress Blanca Portillo on her creative process as she prepares to incarnate Maria of Nazareth in the play Mary's Testament by Colm Toibin and under the direction of Agustin Villaronga.